Trauma in Washington Black’s Character as Seen in Esi Edugyan’s Washington Black - Reynaldi Alexander Agung; Nur Saktiningrum (Universitas Gadjah Mada, 2020)
This research analyzes the effect of trauma on Washington Black, the main character in Esi Edugyan’s Washington Black. Joy DeGruy’s theory of Post Traumatic Slave Syndrome is applied in order to understand how Black’s past experiences, trauma, and slavery affect his life. The primary data used in this research are taken from the novel Washington Black by Esi Edugyan, which includes characterization and description of the character Washington Black found in sentences and paragraphs in the novel. This research shows that Washington Black’s traumatic experiences are the main driving force of his actions which indicates the inability to separate his past from his decisions. The character Washington Black is a perfect model of someone who possesses Post Traumatic Slave Syndrome.